DIAGNOSTICS AND SURGICAL TREATMENT OF SPONDILODISCITES OF THE TREASURAL AND LUMBAR SPINE - Mardanov Jamshid Jahongirovich; Gafarov Jahongir Sobirovich (Scholar Express Journals, 2021)
Spondylodiscitis is an infectious inflammatory disease of the vertebrae and intervertebral discs. Its frequency has increased in recent years. With this disease, two main functions of the spine are disrupted: ensuring a stable vertical position of the trunk and protecting the spinal nerve structures. At the same time, the diagnosis of spondylodiscitis is difficult and often occurs with a significant delay after the onset of the first symptoms. This is due to the rare occurrence of the disease. Spondylodiscitis affects children and adolescents during the period of active growth of the spine, as well as adults after the age of 45-50 years. Men get sick almost 2 times more often than women. The disease is most susceptible to patients with chronic endocrine pathology (especially diabetes mellitus), patients with immunodeficiency who have been taking cytostatic and hormonal therapy for a long time, intravenous drug addicts, and patients who have undergone surgery on the spine. There are various classifications of spondylodiscitis.
Keywords: Spondylodiscitis; Hematogenous infection; Chondroblast; Diagnostic